Predictors of Nasal Obstruction: Quantification and Assessment Using Multiple Grading Scales - Camacho, Macario (Plast Surg Int, 2016)
Objective. To evaluate the association between nasal obstruction and (1) demographic factors, (2) medical history, (3) physical tests, and (4) nasal exam findings. Study Design. Case series. Methods. Chart review at a tertiary medical center. Results. Two hundred-forty consecutive patients (52.1 ± 17.5 years old, with a Nasal Obstruction Symptom Evaluation (NOSE) score of 32.0 ± 24.1) were included. Demographic factors and inferior turbinate sizes were not associated with NOSE score or Nasal Obstruction Visual Analog Scale (NO-VAS). A significant association was found between higher NOSE score on univariate analysis and positive history of nasal trauma (p = 0.0136), allergic rhinitis (p < 0.0001), use of nasal steroids (p = 0.0108), higher grade of external nasal deformity (p = 0.0149), higher internal nasal septal deviation grade (p = 0.0024), and narrow internal nasal valve angle (p < 0.0001). Multivariate analysis identified the following as independent predictors of high NOSE score: NO-VAS: ≥50 (Odds Ratio (OR) = 17.6 (95% CI 5.83–61.6), p < 0.0001), external nasal deformity: grades 2–4 (OR = 4.63 (95% CI 1.14–19.9), p = 0.0339), and allergic rhinitis: yes (OR = 5.5 (95% CI 1.77–18.7), p = 0.0041). Conclusion. Allergic rhinitis, NO-VAS score ≥ 50, and external nasal deformity (grades 2–4) were statistically significant independent predictors of high NOSE scores on multivariate analysis. Inferior turbinate size was not associated with NOSE scores or NO-VAS.